A Comparison of Clinical and Radiological Parameters in the Evaluation of Molar Furcation Involvement in Periodontitis - Sanja Komšić; Darije Plančak; Adrian Kašnaj; Ivan Puhar (University of Zagreb. School of Dental Medicine, 2019)
Objective: The aim of this study was to compare clinical, intra-surgical, 2D (panoramic) and 3D (CBCT)-based parameters in assessing molar furcation involvement (FI). Materials and Methods: Six patients with generalized periodontitis Stage II to IV, Grade B and C who were scheduled for the periodontal flap surgical treatment were recruited in the study. In total, 38 molar teeth with 93 furcation sites were analysed. All subjects had comprehensive periodontal examination, which included an assessment of molar FI using Naber's probe according to modified Glickman's classification. Periodontal surgery was performed in patients with at least one maxillary molar with probing depth of ≥6 mm. This probing demonstrated lower grade of FI compared with intra-surgical findings. Results: Periodontal probing, intra-surgical measurement and measurements based on CBCT significantly correlated with each other regarding the assessment of FI, with r values ranging between 0.81 to 1.00 (p<0.01). The correlation of panoramic radiograph with periodontal probing was 0.49, with CBCT 0.39 and with intra-surgical measurements 0.36. The results showed an excellent agreement and higher accuracy between intra-surgical measurements and CBCT (0.96), in contrast to clinical examination and panoramic radiography- 0.87 and 0.63 respectively. Different clinical and radiological modalities showed a correlation among each other. They are accurate and have their own benefits, which makes (renders) them useful in establishing periodontal diagnosis and treatment planning. Conclusion: However, CBCT offers significant advantages including excellent agreement and higher accuracy and can be used as justified as excellent diagnostic tool in detecting and locating FI to provide a more reliable diagnosis and basis for treatment decisions.